2021
DOI: 10.1037/spy0000202
|View full text |Cite
|
Sign up to set email alerts
|

Pressure training for performance domains: A meta-analysis.

Abstract: 18Funding: This research did not receive any specific grant from funding agencies in the public, 19 commercial, or not-for-profit sectors. 20 21 22 pressurized training environments rather than relying on greater amounts of training to help 39 performers adjust to pressure. Future research should develop practical pressure 40 manipulations, conduct retention tests, and measure performance in competitive or real-life 41 scenarios. 42 43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 48 publications
(98 reference statements)
2
29
0
1
Order By: Relevance
“…sport and medical) revealed that SET significantly improved performance with a moderate effect size ( r = 0.296), which they argue is comparable to other well-established training strategies, such as overlearning and mental rehearsal. Another, more recent meta-analysis that focused on pressure training, which is similar to SET, reported similar results, including for training delivered in the law enforcement context (Low et al , 2020).…”
Section: Scenario-based Trainingmentioning
confidence: 72%
“…sport and medical) revealed that SET significantly improved performance with a moderate effect size ( r = 0.296), which they argue is comparable to other well-established training strategies, such as overlearning and mental rehearsal. Another, more recent meta-analysis that focused on pressure training, which is similar to SET, reported similar results, including for training delivered in the law enforcement context (Low et al , 2020).…”
Section: Scenario-based Trainingmentioning
confidence: 72%
“…Whilst anxiety is an indicator of pressure (e.g., Gucciardi & Dimmock, 2008), it has not been demonstrated that experiencing pressure always results in anxiety. Indeed, Baumeister and Shower's (1986) formative, and widely used (e.g., Low et al, 2020), definition of pressure is relatively neutral (i.e., 'the presence of situational incentives for optimal, maximal, or superior performance ', p. 362). As such, it may not be the case that all clutch performances are preceded by symptoms of anxiety or occur in a state of anxiety.…”
Section: Inadequate Theoretical Frameworkmentioning
confidence: 99%
“…Reviews of interventions intended to help individuals' perform under pressure (e.g., Gr€ opel & Mesagno, 2017;Kent et al, 2018, Low et al, 2020 have identified that coping resources can be developed from adaptive reflection following pressure exposure (Fletcher, 2019). Physically practicing domain-specific skills under simulated pressure is known as pressure training (Low et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of interventions intended to help individuals' perform under pressure (e.g., Gr€ opel & Mesagno, 2017;Kent et al, 2018, Low et al, 2020 have identified that coping resources can be developed from adaptive reflection following pressure exposure (Fletcher, 2019). Physically practicing domain-specific skills under simulated pressure is known as pressure training (Low et al, 2020). Pressure training (PT) may increase the coping repertoire of an individual (e.g., the knowledge of coping strategies available to an individual; such as, performing a penalty in a cup final), develop variation (e.g., ability to select and alternate coping strategies that are more effective; such as, thoughtstopping in a one-v-one tackle) and extend understanding of goodness of fit (e.g., was the coping strategy helpful for performance?)…”
Section: Introductionmentioning
confidence: 99%